CONCEPTUALIZATION OF STUDENT-TEACHER RELATIONSHIP: A COMPARATIVE STUDY OF SYEKH NAWAWI AL-BANTANI AND SYEKH HASYIM ASY'ARI'S THOUGHT - Ahmad Syarifudin; Dimyati Dimyati; Taufik Abdillah Syukur (Jurnal Konseling Pendidikan Islam, 2026)
This study analyzes the conceptualization of student-teacher relationships according to Syekh Nawawi al-Bantani and Syekh Hasyim Asy'ari as a response to the moral crisis in contemporary education. Using a qualitative method with a comparative approach, this research examines Syekh Nawawi's Maraaq al-Ubudiyyah and Syekh Hasyim Asy'ari's Adab al-'Alim wa al-Muta'allim. The findings reveal that Syekh Nawawi employs a principle-minimalist approach with 13 universal moral dimensions, while Syekh Hasyim Asy'ari uses a procedural-maximalist approach with 81 detailed substantive points. Both approaches differ in writing format, theme placement, and level of elaboration, yet both emphasize ta'dhim (respect), tawadhu' (humility), and husn al-adab (good ethics) as foundations for blessed knowledge. This study concludes that integrating both approaches can produce an Islamic education model that is theologically solid, operationally clear, and applicable in addressing modern educational challenges. The relevance of their thoughts to achieving blessed knowledge manifests in forming students' characters who are not only intellectually intelligent but also spiritually mature.